2004
DOI: 10.2165/00002018-200427100-00005
|View full text |Cite
|
Sign up to set email alerts
|

Haematological Effects of Interferon-??-1a (Rebif??) Therapy in Multiple Sclerosis

Abstract: Although haematological abnormalities are common and dose-related in patients with MS receiving interferon-beta-1a, the events are mainly mild and transient, with little impact on adherence to therapy. Haematological events are rarely of clinical significance and do not adversely affect the benefit-to-risk ratio that favours high-dose interferon-beta-1a therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
0
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(48 citation statements)
references
References 30 publications
1
46
0
1
Order By: Relevance
“…In 2 systematic reviews examining hepatic dysfunction in patients receiving IFN β-1a SC tiw that used data from randomized controlled clinical trials and postmarketing surveillance studies, raised hepatic aminotransferase levels were predominately asymptomatic, tended to occur early (within the first 12 months) in treatment, and often were resolved spontaneously or with dosage adjustment. 36,37 Other serious AEs, including Stevens-Johnson syndrome, TTP/HUS, drug-induced lupus erythematosus, autoimmune hepatitis, and urticaria, showed uniformly low IRs. RÍo et al (2005), in an 8-year follow-up study of IFN β patients, found 3 cases of urticaria and angioedema in those taking IFN β-1a SC tiw.…”
Section: ■■ Discussionmentioning
confidence: 99%
“…In 2 systematic reviews examining hepatic dysfunction in patients receiving IFN β-1a SC tiw that used data from randomized controlled clinical trials and postmarketing surveillance studies, raised hepatic aminotransferase levels were predominately asymptomatic, tended to occur early (within the first 12 months) in treatment, and often were resolved spontaneously or with dosage adjustment. 36,37 Other serious AEs, including Stevens-Johnson syndrome, TTP/HUS, drug-induced lupus erythematosus, autoimmune hepatitis, and urticaria, showed uniformly low IRs. RÍo et al (2005), in an 8-year follow-up study of IFN β patients, found 3 cases of urticaria and angioedema in those taking IFN β-1a SC tiw.…”
Section: ■■ Discussionmentioning
confidence: 99%
“…5,44 During the first 6 months of therapy, IFNβ-1a SC was found to be associated with a generally mild doserelated increase in leukopenia, lymphopenia, granulocytopenia, and thrombocytopenia (P < .0001) but not anemia. 45 Leukopenia and lymphopenia were observed in 20% and 29% of patients receiving IFNβ-1a 22 µg SC and 13% and 22% of patients receiving IFNβ-1a 44 µg SC, respectively, over the first 2 years of treatment and 27% and 35% of patients receiving IFNβ-1a 22 µg SC and 16% and 23% of patients of patients receiving IFNβ-1a 44 µg SC, respectively, after 4 years of treatment. 5 After 6 years of follow-up, leukopenia was observed in 14% and lymphopenia in 20% of patients treated with IFNβ-1a SC, most of which was mild.…”
Section: Disease-modifying Therapies Ifnβ β and Glatiramer Acetatementioning
confidence: 97%
“…Severe leukopenia, lymphopenia and neutropenia are uncommon. These alterations are usually early (within 3 months), asymptomatic and not associated with increased risk of infection [15]. The phenomenon is entirely peripheral, with normal bone marrow, as a redistribution of blood cells.…”
Section: Changes In Biochemical Parameters During Therapy With Diseasmentioning
confidence: 99%